Piping Inspection Monitoring Strategy - Mohd Fithri Azad Bin Abul Kalam Azad, Mohd Fithri Azad (Universiti Teknologi Petronas, 2011)
The objective of this project is to develop an inspection planning by applying the thickness measurement method in order to get the remaining life of the piping component/system at the Naphtha hydro-finer line. This is related to the problem occur in order to replace the inspection conventional method to the Risk Base Inspection (RBI) method to analyze the pipe system more efficient.